Lightweight composite material for daily consumer goods and preparation method thereof

By adding glass beads, paraffin oil, polypropylene and low-density inorganic fillers to the thermoplastic elastomer (TPS) material and modifying sepiolite fibers to form composite materials with low density and high mechanical properties, the current solution is solved In some technology, the performance reduction problems caused by the addition of fillers have been achieved, and higher hardness, durability and impact resistance are achieved.

CN119177029APending Publication Date: 2024-12-24JIANGSU TOP POLYMER ENTERPRISE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411539918.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

After the addition of low-density fillers, the mechanical properties and durability of existing thermoplastic elastomer (TPS) materials are reduced, and cannot meet the manufacturing needs of daily consumer goods.

Method used

The raw materials such as styrene thermoplastic elastomer TPS, glass microbeads, paraffin oil, polypropylene, low-density inorganic fillers and sepiolite fibers are used to form a lightweight with low density and high mechanical properties through compounding and modification. Quantify composite materials.

Benefits of technology

It improves the density, hardness, impact resistance, heat resistance and durability of composite materials, extends the service life, and meets the lightweight material needs of daily consumer goods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005112536280000061
    Figure BDA0005112536280000061
  • Figure BDA0005112536280000071
    Figure BDA0005112536280000071
Patent Text Reader

Abstract

The invention relates to the field of materials for daily consumer goods, and particularly discloses a lightweight composite material for daily consumer goods and a preparation method of the lightweight composite material. The lightweight composite material for the consumer goods comprises the following raw materials in parts by weight: 20-30 parts of a styrene thermoplastic elastomer TPS, 10-20 parts of glass beads, 40-60 parts of paraffin oil, 5-15 parts of polypropylene, 3-5 parts of a low-density inorganic filler, 1-3 parts of a foaming agent, 3-5 parts of sepiolite fibers and 1-3 parts of an antioxidant. The lightweight composite material for the daily consumer goods, prepared by the invention, has relatively good hardness and strength, and also keeps relatively low density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of materials for daily consumer products, and in particular to a lightweight composite material for daily consumer products and a preparation method thereof. Background Art

[0002] Lightweight materials are materials that have both the characteristics of light weight and can meet product performance requirements. Parts made of lightweight materials can reduce the overall weight of the product, achieve the purpose of energy conservation and emission reduction, and have both economic and environmental benefits. Thermoplastic elastomer (TPS) materials are widely used in automobiles and daily consumer products due to their good elasticity and processing properties.

[0003] At present, thermoplastic elastomer (TPS) materials are mainly prepared by adding low-density talcum powder into thermoplastic elastomer (TPS) materials to reduce the density of TPS materials. However, the addition of too much filler will lead to reduced mechanical properties and durability of the composite material. After being impacted by external forces during use, the service life of the composite material is significantly shortened, which cannot meet the manufacturing needs of daily consumer goods. Summary of the invention

[0004] In order to improve the density and mechanical properties of existing lightweight composite materials, the present application provides a lightweight composite material for daily consumer products and a preparation method thereof.

[0005] In the first aspect, the present application provides a lightweight composite material for daily consumer products, adopting the following technical solution: a lightweight composite material for daily consumer products, comprising the following raw materials in parts by weight: 20-30 parts of styrene thermoplastic elastomer TPS, 10-20 parts of glass beads, 40-60 parts of paraffin oil, 5-15 parts of polypropylene, 3-5 parts of low-density inorganic filler, 1-3 parts of foaming agent, 3-5 parts of sepiolite fiber, and 1-3 parts of antioxidant.

[0006] By adopting the above technical solution, styrene thermoplastic elastomer TPS as the matrix of the composite material can give the composite material a lower density and better elasticity and impact resistance. The compounding of polypropylene and TPS can improve the hardness and heat deformation resistance of the composite material and improve the mechanical properties of the composite material. Glass microspheres have lower density and rigidity, which can improve the hardness and dimensional stability of the composite material. The spherical structure of glass microspheres helps to reduce stress concentration inside the composite material, reduce the stress compression deformation phenomenon of the composite material, and can also reduce the density of the composite material, so that the composite material has both lower density and higher strength.

[0007] Paraffin oil can reduce the melt viscosity of composite materials, making composite materials easy to process and shape. At the same time, paraffin oil can also improve the flexibility, tear strength and elongation at break of composite materials, reduce the brittleness and cracking of composite materials, and improve the durability of composite materials. Adding a foaming agent to the composite material can decompose and produce gas during the heating process, prompting the formation of a microporous structure inside the composite material, further reducing the density of the composite material and improving the thermal insulation performance of the composite material. Sepiolite fiber has a high aspect ratio, a large specific surface area, and presents fibrous accumulation, which can improve the melt strength of the composite material and prompt the composite material to form uniform and fine bubbles. At the same time, sepiolite fiber has little effect on the density of the composite material, maintaining the low density of the composite material, and is better used in lightweight materials for daily consumer products.

[0008] Preferably, the styrene-based thermoplastic elastomer is a hydrogenated styrene-butadiene block copolymer.

[0009] By adopting the above technical scheme, the butadiene segments in the hydrogenated styrene-butadiene block copolymer are hydrogenated, so that the hydrogenated styrene-butadiene block copolymer has better thermal stability, impact resistance and elasticity, while maintaining a lower density, and can withstand greater mechanical stress in daily consumer products, reduce the phenomenon of compression deformation of composite materials, and improve the deformation resistance and tear resistance of composite materials.

[0010] Preferably, the low-density inorganic filler is at least one of nano calcium carbonate and talcum powder.

[0011] By adopting the above technical solution, compared with other inorganic fillers, the density of nano calcium carbonate and talcum powder is relatively low, which can reduce the density of the composite material, while improving the strength, wear resistance and heat resistance of the composite material and extending the service life of the composite material.

[0012] Preferably, the low-density inorganic filler is modified by unsaturated hydroxy fatty acid, and the modification method comprises the following specific steps: heating the low-density inorganic filler to 70-80° C., then adding unsaturated hydroxy fatty acid and stirring to obtain a modified low-density inorganic filler.

[0013] By adopting the above technical solution, unsaturated hydroxy fatty acid is used to modify low-density inorganic fillers, which can improve the dispersibility of low-density inorganic fillers in the matrix material, enhance the interface bonding between low-density inorganic fillers and matrix materials, and improve the compatibility of composite material systems. The carboxyl groups in the fatty acid molecules can form chemical bonds with the active groups on the surface of the low-density inorganic fillers, while the long chain part of the fatty acid can interact with the molecular chain segments of the styrene thermoplastic elastomer TPS to form bridges, thereby improving the compatibility and interfacial bonding between the filler and the matrix, promoting a more uniform distribution of low-density inorganic fillers in the matrix, reducing stress concentration, and improving the impact toughness and durability of the composite material.

[0014] Preferably, the sepiolite fiber is preliminarily acidified and then organically modified with a quaternary ammonium salt.

[0015] By adopting the above technical solution, pre-acidification of sepiolite fiber can first remove impurities in sepiolite fiber, increase the specific surface area of ​​sepiolite fiber, and enhance the subsequent organic modification effect of sepiolite fiber. Then, quaternary ammonium salt is used to organically modify sepiolite fiber, and quaternary ammonium salt can be intercalated into the interlayer structure of sepiolite fiber, thereby improving the compatibility of sepiolite fiber with polypropylene and styrene thermoplastic elastomer TPS.

[0016] Preferably, the method for doubly modifying sepiolite fiber comprises the following specific steps: The sepiolite fiber is mixed with an acid solution in advance to form a mixed solution A, the mixed solution A is heated to 75-85° C. by microwave, stirred evenly, washed, and dried to obtain the acidified sepiolite fiber; The acidified sepiolite fiber and water are mixed, heated to 60-70°C, dodecyltrimethylammonium bromide and sodium hexametaphosphate are added to react, and then centrifuged, filtered, washed and dried to obtain the double-modified sepiolite fiber.

[0017] Preferably, the foaming agent is heat-expandable microspheres.

[0018] In a second aspect, the present application provides a method for preparing a lightweight composite material for daily consumer products, using the following technical solution: A method for preparing a lightweight composite material for daily consumer products comprises the following specific steps: mixing styrene thermoplastic elastomer TPS, paraffin oil, polypropylene, low-density inorganic filler, sepiolite fiber and antioxidant, then adding glass microbeads for melt extrusion and granulation to obtain a composite material, then mixing the composite material with a foaming agent and performing injection molding to obtain the lightweight composite material for daily consumer products.

[0019] By adopting the above technical solution and combining styrene thermoplastic elastomer TPS and polypropylene, the composite material can be given lower hardness and better elasticity, impact resistance and toughness. At the same time, glass microbeads are used to further reduce the density of the composite material, improve the structural stability of the composite material, and reduce the deformation of the composite material caused by external impact.

[0020] In summary, this application has the following beneficial effects: 1. Since the present application uses low-density styrene thermoplastic elastomer TPS compounded with polypropylene and glass microspheres, the composite material has a lower density and better elasticity and impact resistance. The use of paraffin oil can also improve the flexibility, tear strength and elongation at break of the composite material, and reduce the phenomenon of brittleness and cracking of the composite material.

[0021] 2. In this application, unsaturated hydroxy fatty acids are used to modify low-density inorganic fillers, which can enhance the interface bonding between low-density inorganic fillers and matrix polymers, promote a more uniform distribution of low-density inorganic fillers in the matrix, reduce stress concentration, and improve the impact toughness and durability of composite materials. The sepiolite fiber is pre-modified by acidification and then organically modified by quaternary ammonium salts, which can be better compatible with polypropylene and styrene thermoplastic elastomer TPS matrices. DETAILED DESCRIPTION

[0022] The present application is further described in detail below with reference to the embodiments.

[0023] All raw materials in the examples are commercially available. Example

[0024] Example 1 The present embodiment provides a lightweight composite material for daily consumer goods, including the following raw materials in parts by weight: 25kg of styrene thermoplastic elastomer TPS, 15kg of glass microspheres, 50kg of paraffin oil, 10kg of polypropylene, 4kg of low-density inorganic filler, 2kg of foaming agent, 4kg of sepiolite fiber, and 2kg of antioxidant. The styrene thermoplastic elastomer TPS is a hydrogenated styrene-butadiene block copolymer, which is purchased from Kraton G1701 in the United States, the glass microspheres have a pressure of 15000MPa / Psi, a D90 particle size of 50μm, a polypropylene molecular weight of 80,000, a low-density inorganic filler is talcum powder, and the average particle size of the low-density inorganic filler is 20μm, the foaming agent is a thermal expansion microsphere, and the thermal expansion microsphere is selected from Expancel 930MB120 of Akzo Nobel, and the antioxidant is antioxidant 1010.

[0025] The present embodiment provides a method for preparing a lightweight composite material for daily consumer products, comprising the following specific steps: mixing styrene-based thermoplastic elastomer TPS, paraffin oil, polypropylene, low-density inorganic filler, sepiolite fiber and antioxidant for 20 minutes, then adding glass microbeads, melt-extruding and granulating at 210°C to obtain a composite material, then mixing the composite material and a foaming agent evenly, and injection molding at 200°C to obtain a lightweight composite material for daily consumer products.

[0026] Example 2 The difference between Example 2 and Example 1 is that the amount of styrene thermoplastic elastomer TPS used in the composite material raw material is 20 kg, the amount of glass microspheres used is 10 kg, the amount of paraffin oil used is 40 kg, the amount of polypropylene used is 15 kg, the amount of low-density inorganic filler used is 3 kg, the amount of foaming agent used is 1 kg, the amount of sepiolite fiber used is 3 kg, and the amount of antioxidant used is 1 kg.

[0027] Example 3 The difference between Example 3 and Example 1 is that the amount of styrene thermoplastic elastomer TPS used in the composite material raw material is 30 kg, the amount of glass microspheres used is 20 kg, the amount of paraffin oil used is 60 kg, the amount of polypropylene used is 5 kg, the amount of low-density inorganic filler used is 5 kg, the amount of foaming agent used is 3 kg, the amount of sepiolite fiber used is 5 kg, and the amount of antioxidant used is 3 kg.

[0028] Example 4 The difference between Example 4 and Example 1 is that the styrene thermoplastic elastomer TPS in the composite material raw material is a styrene-butadiene-styrene triblock copolymer LG501.

[0029] Example 5 The difference between Example 5 and Example 1 is that the low-density inorganic filler in the composite material raw material is nano-calcium carbonate, and the average particle size of the nano-calcium carbonate is 100 nm.

[0030] Example 6 The difference between Example 6 and Example 1 is that the low-density inorganic filler in the composite material raw material is a mixture of nano-calcium carbonate and talcum powder, the mass ratio of nano-calcium carbonate to talcum powder is 1:1, and the average particle size of the low-density inorganic filler is 20 μm.

[0031] Example 7 The difference between Example 7 and Example 6 is that the low-density inorganic filler in the composite material raw material is modified by unsaturated hydroxy fatty acid, wherein the unsaturated hydroxy fatty acid is 12-hydroxyoleic acid. The method for preparing a lightweight composite material for daily consumer products comprises the following specific steps: S1: Heat the low-density inorganic filler to 75° C., then add unsaturated hydroxy fatty acid and stir at a speed of 1000 r / min for 15 minutes to obtain a modified low-density inorganic filler.

[0032] S2: Styrene thermoplastic elastomer TPS, paraffin oil, polypropylene, modified low-density inorganic filler, sepiolite fiber and antioxidant are mixed for 20 minutes, and then glass microbeads are added, melt-extruded and granulated at 210°C to obtain a composite material, and then the composite material is evenly mixed with a foaming agent, and injection molded at 200°C to obtain a lightweight composite material for daily consumer products.

[0033] Example 8 The difference between Example 8 and Example 7 is that the sepiolite fibers in the raw material of the composite material are preliminarily acidified and then organically modified with quaternary ammonium salt.

[0034] A method for preparing a lightweight composite material for daily consumer products comprises the following specific steps: S1: Heat the low-density inorganic filler to 75° C., then add unsaturated hydroxy fatty acid and stir at a speed of 1000 r / min for 15 minutes to obtain a modified low-density inorganic filler.

[0035] S2: Mix sepiolite fiber with hydrochloric acid solution and water, wherein the concentration of the hydrochloric acid solution is 1.2 ml / L, and the mass ratio of sepiolite fiber, hydrochloric acid solution and water is 1:15:5, to form a mixed solution A, and microwave heat the mixed solution A to 80° C. at a power of 1000 W, stir for 2 hours, remove the mixture, wash it, and dry it to obtain the acidified sepiolite fiber.

[0036] S3: Mix the acidified sepiolite fiber and water, the mass ratio of the acidified sepiolite fiber to water is 1:20, heat to 65°C, add dodecyltrimethylammonium bromide and sodium hexametaphosphate to react for 5 hours, the mass ratio of the acidified sepiolite fiber, dodecyltrimethylammonium bromide and sodium hexametaphosphate is 1:0.5:0.1, then centrifuge, filter, wash and dry to obtain the double-modified sepiolite fiber.

[0037] S4: Styrene thermoplastic elastomer TPS, paraffin oil, polypropylene, modified low-density inorganic filler, double-modified sepiolite fiber and antioxidant are mixed for 20 minutes, and then glass microbeads are added, melt-extruded and granulated at 210°C to obtain a composite material, and then the composite material is evenly mixed with a foaming agent, and injection molding is performed at 200°C to obtain a lightweight composite material for daily consumer products.

[0038] Example 9 The difference between Example 9 and Example 8 is that the sepiolite fiber in the composite material raw material is not acidified and modified.

[0039] A method for preparing a lightweight composite material for daily consumer products comprises the following specific steps: S1: Heat the low-density inorganic filler to 75° C., then add unsaturated hydroxy fatty acid and stir at a speed of 1000 r / min for 15 minutes to obtain a modified low-density inorganic filler.

[0040] S2: Mix sepiolite fiber and water, the mass ratio of sepiolite fiber to water is 1:20, heat to 65°C, add dodecyltrimethylammonium bromide and sodium hexametaphosphate to react for 5 hours, the mass ratio of sepiolite fiber, dodecyltrimethylammonium bromide and sodium hexametaphosphate is 1:0.5:0.1, then centrifuge, filter, wash and dry to obtain modified sepiolite fiber.

[0041] S3: Styrene thermoplastic elastomer TPS, paraffin oil, polypropylene, modified low-density inorganic filler, modified sepiolite fiber and antioxidant are mixed for 20 minutes, and then glass microbeads are added, melt-extruded and granulated at 210°C to obtain a composite material, and then the composite material is evenly mixed with a foaming agent, and injection molded at 200°C to obtain a lightweight composite material for daily consumer products.

[0042] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no glass microspheres are used in the composite material raw material.

[0043] A method for preparing a lightweight composite material for daily consumer products comprises the following specific steps: Styrene thermoplastic elastomer TPS, paraffin oil, polypropylene, low-density inorganic filler, sepiolite fiber and antioxidant are mixed for 20 minutes, melt-extruded and granulated at 210°C to obtain a composite material, and then the composite material is evenly mixed with a foaming agent and injection molded at 200°C to obtain a lightweight composite material for daily consumer products.

[0044] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that glass microspheres and polypropylene are not used in the raw materials of the composite material.

[0045] Performance testing According to the lightweight composite materials for daily consumer products provided in Examples 1-9 and Comparative Examples 1-2 of the present application, the following performance tests were performed, and the specific test results are shown in Table 1.

[0046] Detection Methods 1. Density determination The density of the lightweight composite material for daily consumer products prepared in the present application was tested with reference to the standard of ISO-1183-1 "Determination of density of plastics other than foamed plastics".

[0047] 2. Hardness According to ISO 7619-1:2010 Rubber, vulcanized or thermoplastic - Determination of indentation hardness - Part 1: Hardness technique (Shore hardness)", the test conditions are: room temperature and 15S delay.

[0048] 3. Compression set The test was carried out according to the standard of ASTM D-695 "Plastic Compression Test" and the test conditions were 70℃ / 22h.

[0049] 4. Elongation at break and tear strength With reference to ASTM D-412 "Rubber and Elastomer Tensile Test Standard", the elongation at break of the lightweight composite material for daily consumer products prepared in this application was tested, and with reference to ASTM D-624 "Rubber and Elastomer Tear Strength Test Standard", the tear strength of the lightweight composite material for daily consumer products prepared in this application was tested.

[0050] Table 1: Performance test results data table It can be seen from the performance test results that the lightweight composite material for daily consumer products prepared in this application can promote the composite material to have better mechanical properties, give the composite material higher hardness and strength, and reduce the phenomenon of stress deformation of the composite material in the application of lightweight materials for daily consumer products while maintaining a relatively low density. By comparing Example 4 with Example 1, it can be seen that the composite material prepared by the hydrogenated styrene-butadiene block copolymer used in Example 1 has a lower density, and is more in line with the requirements of plastic reduction and environmental protection when used in the field of lightweight materials for daily consumer products.

[0051] It can be seen from Example 7 that the low-density inorganic filler used in the present application is modified with unsaturated hydroxy fatty acids. From the performance test results, it can be seen that the prepared composite material has a lower density and better strength, which further illustrates that after modification with unsaturated hydroxy fatty acids, the low-density inorganic filler can be evenly dispersed in the composite material system, uniformly improving the hardness and compression deformation resistance of the composite material.

[0052] It can be seen from Examples 8-9 that the sepiolite fiber is modified, and the comprehensive performance of the composite material prepared in Example 8 is better. The pre-acidification modification and then the organic modification with quaternary ammonium salt can better improve the compatibility of the sepiolite fiber and the composite material matrix, thereby improving the elongation at break and the tear strength of the composite material.

[0053] By comparing Comparative Examples 1-2 with Example 1, it can be seen that glass microspheres are not used in the raw materials of the composite material of Comparative Example 1, and glass microspheres and polypropylene are not used in the raw materials of the composite material of Comparative Example 2. From the performance test results, it can be seen that the comprehensive performance of the prepared composite material is significantly reduced, the density of the composite material increases, and it gradually does not meet the requirements of lightweight application materials for daily consumer products. At the same time, the strength and hardness of the composite material are also reduced, and the durability of the composite material is also significantly reduced. It further shows that glass microspheres can improve the strength and hardness of the composite material while further reducing the density of the composite material.

[0054] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A lightweight composite material for daily consumer products, characterized in that: The invention comprises the following raw materials in parts by weight: 20-30 parts of styrene thermoplastic elastomer TPS, 10-20 parts of glass microspheres, 40-60 parts of paraffin oil, 5-15 parts of polypropylene, 3-5 parts of low-density inorganic filler, 1-3 parts of foaming agent, 3-5 parts of sepiolite fiber and 1-3 parts of antioxidant.

2. The lightweight composite material for daily consumer products according to claim 1, characterized in that: The styrene-based thermoplastic elastomer is a hydrogenated styrene-butadiene block copolymer.

3. The lightweight composite material for daily consumer products according to claim 1, characterized in that: The low-density inorganic filler is at least one of nano calcium carbonate and talcum powder.

4. The lightweight composite material for daily consumer products according to claim 3, characterized in that: The low-density inorganic filler is modified by unsaturated hydroxy fatty acid, and the modification method comprises the following specific steps: heating the low-density inorganic filler to 70-80° C., then adding unsaturated hydroxy fatty acid and stirring to obtain a modified low-density inorganic filler.

5. The lightweight composite material for daily consumer products according to claim 1, characterized in that: The sepiolite fiber is preliminarily acidified and then organically modified with quaternary ammonium salt.

6. The lightweight composite material for daily consumer products according to claim 5, characterized in that: The method for doubly modifying sepiolite fiber comprises the following specific steps: The sepiolite fiber is mixed with an acid solution in advance to form a mixed solution A, the mixed solution A is heated to 75-85° C. by microwave, stirred evenly, washed, and dried to obtain the acidified sepiolite fiber; The acidified sepiolite fiber and water are mixed, heated to 60-70°C, dodecyltrimethylammonium bromide and sodium hexametaphosphate are added to react, and then centrifuged, filtered, washed and dried to obtain the double-modified sepiolite fiber.

7. The lightweight composite material for daily consumer products according to claim 1, characterized in that: The foaming agent is heat-expandable microspheres.

8. A method for preparing a lightweight composite material for daily consumer products according to any one of claims 1 to 7, characterized in that: The method comprises the following specific steps: mixing styrene thermoplastic elastomer TPS, paraffin oil, polypropylene, low-density inorganic filler, sepiolite fiber and antioxidant, then adding glass microbeads for melt extrusion and granulation to obtain a composite material, then mixing the composite material with a foaming agent and performing injection molding to obtain a lightweight composite material for daily consumer products.

Citation Information

Cited By

  • Lightweight high-strength concrete and assembled cable well prepared from same

    CN120841905A

  • Lightweight high-strength concrete and fabricated cable well prepared by using same

    CN120841905B